Instrumen Audit Kualitas Rekam Medis Elektronik Menggunakan Content Validity Index (CVI) - Yuniana Eka Pratiwi; Hosizah Hosizah; Sri Jumiati Agustina (Politeknik Negeri Jember, 2026)
Although the National Brain Center Hospital Prof. Dr. Mahar Mardjono Jakarta has implemented an Electronic Medical Record (EMR) system, the quality of its data has not yet met the completeness standards established by the Indonesian Ministry of Health. As the hospital's most prevalent condition, ischemic stroke requires accurate and complete medical documentation to support effective clinical decision-making. Therefore, a comprehensive EMR audit instrument is needed to systematically evaluate data quality. This study aimed to develop and validate an EMR data quality audit instrument for ischemic stroke patients. A Research and Development (R&D) design was employed using the Data Quality Management (DQM) framework based on the data quality characteristics defined by the American Health Information Management Association. The instrument was validated by six experts using the Content Validity Index (CVI), including the Item-Level Content Validity Index (I-CVI) and the Scale-Level Content Validity Index (S-CVI), with indicators derived from the ischemic stroke clinical pathway. The validation results showed I-CVI values ranging from 0.83 to 1.00 and an S-CVI value of 0.99, indicating excellent content validity. The instrument is therefore considered highly valid and suitable for systematic EMR data quality audits to improve the quality of medical documentation.